Solve Your Challenges with Your Teams: Driving Leadership, Innovation and Smart Decisions with the VCW Meta Framework - Lages, L. F.; Dias, Á. (2025)
The VCW solves strategic challenges from within and beyond by empowering teams and aligning stakeholders to succeed. At its core, the VCW acknowledges that some of the most valuable insights and solutions already exist within the organization among employees, teams, and partners who are closest to the challenges. Rather than relying solely on top-down decision-making, the framework engages internal stakeholders through a structured co-creation process that builds ownership, motivation, and alignment. By activating diverse perspectives across departments and levels, leaders are better equipped to drive innovation, leadership, and smart decision-making from the inside out. This enables organizations to move from fragmented efforts to unified action with clear direction and commitment.